If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.3333(2x + -5) = 3 Reorder the terms: 0.3333(-5 + 2x) = 3 (-5 * 0.3333 + 2x * 0.3333) = 3 (-1.6665 + 0.6666x) = 3 Solving -1.6665 + 0.6666x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '1.6665' to each side of the equation. -1.6665 + 1.6665 + 0.6666x = 3 + 1.6665 Combine like terms: -1.6665 + 1.6665 = 0.0000 0.0000 + 0.6666x = 3 + 1.6665 0.6666x = 3 + 1.6665 Combine like terms: 3 + 1.6665 = 4.6665 0.6666x = 4.6665 Divide each side by '0.6666'. x = 7.000450045 Simplifying x = 7.000450045
| (4x-12)=(2y+16) | | 16+5z=-4 | | 4+65x=39x+10 | | 11+-3= | | 4x+6=-50-4x | | 9+3(x+2)=21 | | a*5+71=a*9-5 | | 2(q+3)=1 | | 8y-2=-8 | | -22+7= | | 0.625x+0.75=7 | | 8+-7= | | 3(x+1)+7(x+3)=64 | | 23-(7)= | | 8a(4b)(4)= | | -22-(7)= | | F(x)=x^2+6x+34 | | X+4=3+3x | | 2x^2-46= | | 7(k-3)=3k-6 | | (34)3=3 | | z=b-y | | 3x+50=6x-25 | | 7x-1=4x+1 | | Y-(12)=5 | | 9h+7=97 | | -2+1=m-8 | | 25x-9x^3=0 | | 2(-x-3)*7-3x=-8 | | 8x+9=4x+53 | | 10m-27=43 | | 2(-x)*7-3x=-8 |